2023
DOI: 10.1002/jcph.2333
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Modeling Using Real‐World Data to Optimize Unfractionated Heparin Dosing in Pediatric Patients on Extracorporeal Membrane Oxygenation and Evaluate Target Achievement–Clinical Outcomes Relationship

Abstract: Unfractionated heparin (UFH) is a commonly used anticoagulant for pediatric patients undergoing extracorporeal membrane oxygenation (ECMO) but evidence is lacking on the ideal dosing. We aimed to: (i) develop a population pharmacokinetic (PK) model for UFH, measured through anti‐factor Xa assay, (ii) optimize UFH starting infusions and dose titrations through simulations, and (iii) explore UFH exposure‐clinical outcomes relationship. Data from 218 patients admitted to Utah's Primary Children's Hospital were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 43 publications
(120 reference statements)
1
2
1
Order By: Relevance
“…Secondly, the UFH administration pattern with prolonged continuous infusion and few boluses was challenging for V estimation. However, interpatient variability for V and CL in our final model was lower than in Salem’s study [ 23 ] (75.3 versus 262.9% and 52.4 versus 58.9%, respectively). The residual variability could also be explained by unidentified factors or those known to interact with UFH, among which are antithrombin [ 11 ] or Von Willebrand factor [ 31 ].…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Secondly, the UFH administration pattern with prolonged continuous infusion and few boluses was challenging for V estimation. However, interpatient variability for V and CL in our final model was lower than in Salem’s study [ 23 ] (75.3 versus 262.9% and 52.4 versus 58.9%, respectively). The residual variability could also be explained by unidentified factors or those known to interact with UFH, among which are antithrombin [ 11 ] or Von Willebrand factor [ 31 ].…”
Section: Discussioncontrasting
confidence: 72%
“…In the current study, several covariates were identified to explain UFH PK variability. Firstly, baseline BW was acknowledged to explain interpatient variability for V, confirming existing literature describing the need to individualize the UFH loading dose according to BW in CPB or ECMO [ 22 , 23 ]. Secondly, SCr, a surrogate of glomerular filtration capabilities or CRRT filtration performance, influenced UFH exposure.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations